Guardian Hosts and Custodial Witnesses: In loco parentis in Women's Ghost Stories, 1852–1920. Issue 4 (2nd October 2021) - Baker, Jen
ABSTRACT: In the mid nineteenthcentury, a subgenre of ghost stories emerged that had roots in a hybrid tradition of institutional religious doctrine and oral folkloric expressions of anxiety over the fate of the child's soul in the afterlife. Given the persistently high infant mortality rates and increased public awareness of child abuse across the classes, the growing presence of stranded child ghosts in literary fictions of the period represents, I suggest, doubts or fears over the newly dominant liberal insistence that all children would attain peace in heaven and would be reunited and cared for by their family, as well as looked after by God. The child in this period represents the completion of the domestic and gendered ideal and various non-fiction and fiction literatures urged a sense of community care and guardianship over the living child that was extended to its dead spirit. In a great number of ghost stories by well-known and obscure Anglophone women writers, childless female and male protagonists and narrators act as witnesses for, or saviours of, the orphaned ghost child in ways that reframe or interrogate prescribed ideals regarding motherhood, fatherhood, the spinster, and the bachelor, but which simultaneously project concerns over childlessness and childhood more widely.